Magma–magma interaction in the mantle recorded by megacrysts from Cenozoic basalts in eastern China. Issue 6 (13th April 2019) - Yu, Xun; Zeng, Gang; Chen, Li-Hui; Hu, Sen-Lin; Yu, Zhi-Qiang
ABSTRACT: Recently, besides magma–rock and rock–rock reaction, magma–magma interaction at mantle depth has been proposed as an alternative mechanism to produce diverse compositions of mantle. Clinopyroxene and garnet megacrysts can be formed at this condition since this process is suggested to trigger the high-pressure crystallization of these minerals. Studying on this type of megacrysts provides us important information on the genesis of intraplate basalts and the chemical heterogeneity of mantle, which has not been reported before. Here we present major, trace elements and Sr isotopes of clinopyroxene and garnet megacrysts hosted by Cenozoic basalts from Penglai, Shandong province of eastern China. The megacrysts are suggested to be formed by crystallization from magma because of their moderate Mg # (74.0–79.9 for clinopyroxene and 58.8–65.0 for garnet) and good correlations between Mg # and other elements (e.g. CaO, TiO2, Nd and Lu). The potential crystallized temperature and pressure are estimated to be 1156°C at 2.6–3.2 GPa, which should occur at the top of asthenosphere or lithosphere–asthenosphere boundary based on the lithospheric thickness in this area ( 60–70 km). Since the megacrysts show variable Sr isotopes, and their primary magmas show negative correlation between 87 Sr/ 86 Sr and Hf/Sm ratios, as well as positive correlation between Ba/Th and Nb/U for clinopyroxenes, it indicates a mixing origin. Cenozoic basalts from Shandong show a mixing trend, and high-pressure fractionation of clinopyroxene and garnet is suggested to occur during the mixing process because some basalts show significantly higher Sm/Yb and lower Ca/Al ratios than others, which again supports our interpretations. When compared to megacrysts and host basalts from other locations of eastern China, similar geochemical variations and a deviation trend relative to the mixing trend are also observed. It indicates that magma–magma interaction can be a common process for formation of intraplate basalts and basalt-borne megacrysts.